Creating Value of Agro-Industrial Wastes - Khuriyati, Nafis; Purwadi, Didik; F.A., Ibnu Wahid; Fitriani, Kartika; I.D., I Putu Eldwin (KnE Life Sciences, 2018)
Food processing industry as a kind of agro-industry generates a large amount of waste. These wastes have potential since the contain vitamins, mineral nutrients, and other compounds with functional properties. This paper addresses the wastes generated from processing jackfruit and tuna industries. It was observed that the product development is an important role for creating the value of agro-industrial wastes. The wastes can be used as valuable resources for food production. Jackfruit seed and tuna skin were processed into nutritional foods. Keywords: Agro-Industrial Wastes; Food; Product Development; Value